Pain and Anxiety Reduction of First Stage Maternity Mothers using SEFT Intervention - Sri Mumpuni Yuniarsih; Helwiyah Ropi; Ida Maryati (Pena Jurnal Ilmu Pengetahuan Dan Teknologi, 2015)
Pain and anxiety are major problems in childbirth. Management of pain and anxiety made to smooth the process of childbirth. This study aimed to compare the effect of spiritual intervention and Spiritual Emotional Freedom Technique (SEFT) to reduce both pain and anxiety. The study design used was quasy experiment with consecutive sampling technique. The subjects involved were  36  mothers  giving  birth  at  health  centers  PONED  Pekalongan  which  divided  into  two groups,  SEFT  intervention  as  intervension  group  and  spiritual  intervention  as  control  group. The instrument used was numeric rating scale. Data were analyzed using the Mann Whitney U test,  Wilcoxon  and  Independent  t  Test.  The  results  showed  there  were  differences  in  average decrease  in  pain  and  anxiety  between two groups.  SEFT  intervention proven  to reduce  pain intensity  of  the  first  stage  and  maternal  anxiety was better  than  spiritual  intervention. Keywords: Anxiety, Pain childbirth, Spiritual Emotional Freedom Technique (SEFT).